Teachers in Times of Pandemic: An Ethnological Analysis of Coping with the Challenges in the New Normal - Gilbert Millena; Maricar Magcalen (Philippine Association of Institutions for Research, Inc., 2024)
People are living in the midst of what is the greatest danger in the course of our lives to worldwide instruction, a massive instructive emergency. The study analyzed the lived experiences of the nine teachers in one of the public elementary schools in the province of Albay, Philippines, regarding the challenges they encountered in the preparation and delivery of instructions in time for the "New Normal." Primarily, this research investigated the stress brought by the shift to the "new normal" system of education from the traditional face-to-face delivery of learning to the teachers of Matnog Elementary School, Daraga North District, Daraga, Albay. Ethnographic research was utilized to analyze the lived experiences of the respondents involved. The study found that the shift to teaching brought much stress on the part of the teachers, especially those who are not fond of using technology-based instruction. As to how the teachers cope, it was revealed that all available means and resources were tapped in order to be successful and deliver the learning to its clientele. The study concludes that any form of abrupt changes or adaptation of any system will result in anxiety for those on the front line who were expected to deliver the system by all means.